The effectiveness of using strength exercises with some aids to improve the level of physical fitness and the performance of the approaches and advancement stages in the effectiveness of pole vaulting - AhlamShaghatiMuhsen (International Journal of Psychosocial Rehabilitation, 2020)
The sports field is one of the fields in society that is concerned with the use of auxiliary tools, whose use has become an essential thing in the educational process through their various uses in education and improving performance, in addition to their effective impact in developing the level of performance and achievement among students. Where the research aimed to prepare strength exercises using tools to assist in the effectiveness of pole vaulting for students and to know its impact on the level of performance. The research problem focused on the researcher’s observation while teaching the subject of athletics, especially the effectiveness of pole vaulting and the difficulty of mastering the performance of the technical stages by most students for this activity because this activity contains complex and complex movements, which makes it difficult for students to perform for fear of injury, especially as it is performed using a tool (the pole), which weakens the performance. In addition, the weakness of some of their physical characteristics. The researcher assumed that there are significant differences in the physical tests. And there are statistically significant differences between the pre- and post-tests for the two experimental and control groups in the physical tests. And that there are statistically significant differences between the experimental and control groups in the post-tests in favor of the experimental group.